(untitled) (Prosiding Keislaman dan Sains, 2025)
Islamic boarding schools are recognized as educational institutions rooted in the original culture of the Indonesian nation, reflecting a close connection with local traditions and values. In this digital era, Islamic boarding schools face challenges that require adaptation and expectations but must still maintain their traditional values. The application of hybrid methods to learning in Islamic boarding schools in order to align with the progress of the times is hampered by the limitations of technology or facilities that use digital-based learning media themselves. This research aims to examine the concept of hybrid method innovation, namely the integration of traditional and digital learning packages in Islamic boarding schools. The method used in this research is literature study and observation of its implementation in the Islamic boarding school environment. The research results show that the hybrid learning method not only enriches the learning experience of students, but also prepares them to face an increasingly complex and technology-based world. With the right approach, the hybrid method can be a solution that can accompany students to become superior, creative, have good morals and are competent in religious knowledge and technology so that they are ready to become leaders to face problems in society.